Intergenerational Discounting and Inequality - Frikk Nesje; Paolo G. Piacquadio (CESifo GmbH, 2025)
We study all theories of justice that disentangle ethical views on intergenerational discounting and intergenerational inequality. Each "modular" social welfare function is uniquely identified by a time-discounting function—capturing attitudes toward time—and an aggregator function— capturing attitudes toward inequality. Our axiomatic characterization identifies the properties and establishes the limits of disentangling discounting and inequality. Our theories include as special cases the most common welfare criteria adopted in the literature, while uncovering unexplored (and yet tractable) families of alternative criteria.
Keywords: D30; D60; H43; I31; Q50; 330; intergenerational justice; discounting; inequality